Anaerobic Digestion in the Presence of Antimicrobials—Characteristics of Its Parameters and the Structure of Methanogens - Małgorzata Czatzkowska; Izabela Wolak; Ewa Korzeniewska; Monika Harnisz (Applied Sciences, 2022)
Antibiotics are widely used in human and veterinary medicine, and they are accumulated in various types of waste, including sewage sludge (SS) and cattle slurry (CS), processed by anaerobic digestion (AD). Anaerobic treatment is a method enabling the stabilization of these substrates before transferring to the environment. The presence of contaminants, such as antimicrobials, in organic substrates processed by AD is not regulated by law. The accumulation of antimicrobials in SS and CS is a crucial issue because it may reduce the effectiveness of their stabilization. This study aimed to evaluate the long-term impact of growing concentrations of a mixture of antibiotics on the AD of SS and CS. Methane (CH4) yield, which is the main indicator of the efficiency of AD, was determined. Antibiotic exposure significantly decreased CH4 production only in SS (by 5–8% relative to control; p < 0.05). The copy numbers of the mcrA gene, a functional marker of methanogenesis, were not reliable indicators of CH4 yields in either substrate. During long-term AD, the average concentrations of the mcrA gene were determined at 108 in 1 g of SS digestate and from 108 to 109 in 1 g of CS digestate samples. At the end of long-term AD, methanogens belonging to the family Methanosarcinaceae were more prevalent than methanogens of the family Methanosaetaceae both in SS and CS samples (107 and 108–109 gene copies in 1 g of digestate, respectively).